Ring A-modified Derivatives from the Natural Triterpene 3-O-acetyl-11-keto-β-Boswellic Acid and their Cytotoxic Activity - Li, Tao; Fan, Peihong; Ye, Yaqing; Luo, Qian; Lou, Hongxiang (Anti-Cancer Agents in Medicinal Chemistry, 2017)
Background: Natural triterpene boswellic acids (BAs) have attracted much interest due to their anticancer activity, but more chemical modification is necessary to explore their pharmacological value. In addition to subtle functionalization, transformations that alter the triterpene skeleton are viewed as an alternative approach. Objective: In this study, transformations altering ring A of 3-O-acetyl-11-keto-β-boswellic acid (AKBA) were performed to obtain A-lactone, A-lactam, A-seco and A-contracted derivatives. Method: Thirty-two new derivatives were synthesized, and their structures were confirmed by NMR and MS. Their anticancer activity against human cancer cell lines K562, PC3, A549 and HL60 was screened. Results: Biological evaluation indicated that the ring A cleavage or contraction transformations themselves did not significantly enhance the cytotoxic activity, but most of the derivatives based on these ring A-modified skeletons exhibited good cytotoxic activity. Significantly improved cytotoxicity was discovered for the esterified analogues of the A-lactone and A-lactam series and the amidated analogues of the A-seco and ring A contracted series, especially those bearing two nitrogen-containing substituents. Among them, compounds 6a, 11b, 12k and 18e showed strong cytotoxic activity, with IC50 values of 5.0 3.5 μM against K562 cells, almost ninefold stronger than that of AKBA. Further study proposed that the antiproliferative activities of 6a, 11b, 12k and 18e may be due to apoptosis induction. Conclusion: The transformations of the ring A skeleton of AKBA provide new platforms to discover anticancer candidates.
Keywords: ring A contraction